GE_GERICHTE C/839/2015 vom 3. September 2015 - GE Cour de justice (2015)
VOIE DE DROIT; VALEUR LITIGIEUSE; CONTESTATION DU CONGÉ; CHOSE LOUÉE; CALCUL DU DÉLAI; PÉREMPTION; ABUS DE DROIT | CO.253a.1; CO.273.1; CC.2.2; CO.266l.2; OBLF.9.1.d